Reflections on craft research for and through design - Sellen, Abigail (Proceedings of the 8th Nordic Conference on Human-Computer Interaction, 2014)
As design practice has become more integrated in HCI research, there are on-going discussions around the role of design in research. Design research may take different forms, among which 'Research for Design' and 'Research through Design'. While, by definition, these two differ in their focus and result- The first informs the creation of a design artefact and the second aims for a contribution to knowledge-this paper presents a case study of design research in which Research for and through Design were used iteratively to gain insight into hybrid craft-an integrated physical-digital craft form. Based on our own reflections, this paper discusses what different roles these two strategies may play depending on the research topic under study; the phase in the design process; and the level of abstraction of the research activity and knowledge gained. It thus argues that using Research for and through Design together is a powerful strategy.